PENDUGAAN BESARNYA LIMBAH INDUSTRI PERKAYUAN DI KALIMANTAN SELATAN DAN KEMUNGKINAN PEMANFAATANNYA SEBAGAI SUMBER ENERGI - Han Roliadi; Buharman Buharman (Jurnal Penelitian Hasil Hutan, 1985)
The  volume  of  wood  waste from  sawmills and plywood mills in South  Kalimantan  was estimated  using the regression method. Data  were  collected   from sample mills  in the province.       Based on  the  regression analysis,  the estimated volume  of  sawmill waste generated by sawmills in South Kalimantan during the 1981 - 1982 period  was 684,353 m3 per year, and that of plywood mill was 221,818 m3 per year.       The total wood  waste could produced heat energy (fuel) as much as 12.29  x 1011k.cal/year, or 5.42 x 109 KWH per year  of  electric  energy.